Best Practices for Smoking Cessation Interventions in Primary Care - Andrew McIvor; John Kayser; Jean-Marc Assaad; Gerald Brosky; Penny Demarest; Philippe Desmarais; Christine Hampson; Milan Khara; Ratsamy Pathammavong; Robert Weinberg (Canadian Respiratory Journal)
BACKGROUND: In Canada, smoking is the leading preventable cause of premature death. Family physicians and nurse practitioners are uniquely positioned to initiate smoking cessation. Because smoking is a chronic addiction, repeated, opportunity-based interventions are most effective in addressing physical dependence and modifying deeply ingrained patterns of beliefs and behaviour. However, only a small minority of family physicians provide thorough smoking cessation counselling and less than one-half offer adjunct support to patients.